From Lunch Money to Literary Movement: Evolution of Madan Puraskar Library - Thapa, Ashok (Access: An International Journal of Nepal Library Association, 2025)
Nepal's leading literary archive in the present day, the Madan Puraskar Pustakalaya (MPP), has humble origins in a minor act of selflessness of a schoolboy, Kamal Mani Dixit, in the late 1930s. In this research, the transformation of a grassroots initiative into a national literary institution and its profound cultural, historical, and intellectual significance are traced. A qualitative research design was employed, leveraging archival documents kept at the MPP, including manuscripts, personal files, and rare materials. Secondary literature, biographies, and semi-structured interviews among scholars, employees, and literary writers were employed to gather supporting data. The theoretical perspective combines institutional theory and cultural memory studies to assess the development, legitimacy, and function of the library as a cultural institution. Findings indicate that Kamal Mani Dixit's initial collection of books was formalized by the establishment of the Madan Puraskar Library and its associated Guthi, with significant assistance from Queen Jagadamba Kumari Devi. Over the decades, the library became a center of intellectual activity that preserves Nepal's literary heritage, promotes language development, and provides for public discourse. Important initiatives such as the institution of Madan Puraskar and Jagadamba Shree Puraskar, the computerization of far-flung archives, and the creation of Nepali Unicode font demonstrate the library's dynamic role in maintaining culture and advancing innovation. From an institutional theory perspective, the library demonstrates how casual individual values and activities mature into formal, respected institutions by means of cultural congruence and ongoing dedication. Cultural memory theory highlights its role of preserving collective identity and histories. The trajectory of the MPP highlights the revolutionary potential of private passion when combined with social vision, as a replicable model for memory institutions of developing societies.